Generalist medicine and the U.S. health system (Jossey-Bass, 2004)
Generalist Medicine and U.S. Health Policy contains new contributions from preeminent authorities and a selection of groundbreaking articles and reports from the past forty years. Generalist Medicine and U.S. Health Policy covers a broad range of topics that: examines the current challenges of primary care and generalist medicine, offers a chronological history of the growth of generalist medicine since the 1950s, reviews the models of care on which generalist medicine is based and analyzes the growt.